Job Mobility Networks and Endogenous Labor Markets - Jan Sebastian Nimczik (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
I introduce a novel method to identify endogenous labor markets revealed by job mobility flows. The estimation is based on tools from network analysis. Firms are in the same market if they have similar links to other firms and not because they are located in the same region. I compare endogenous markets to geographically separated markets. I analyze employment spillovers following a large local labor demand shock as well as mobility responses to import competition from China and Eastern Europe.
Keywords: J61; 330